2020
DOI: 10.1557/jmr.2020.18
|View full text |Cite
|
Sign up to set email alerts
|

First-principles identification of localized trap states in polymer nanocomposite interfaces

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Out of chemical defect-containing polymers, the technique was applied to probe electronic properties of various polymers as Polystyrene, Poly(methyl methacrylate), or Poly(ethylene terephthalate) [227], fluorinated polymers [228] and Polyimide [229] that contain unsaturated bonds. It was also extended to interfaces in nanocomposites [230,231]. A step forward with modelling approaches is being achieved with combining density functional theory and GW-BSE (GW-Belthe-Salpeter equation) in order to compute the optical properties of materials, in particular energy levels involved in excited states [232,233].…”
Section: Discussionmentioning
confidence: 99%
“…Out of chemical defect-containing polymers, the technique was applied to probe electronic properties of various polymers as Polystyrene, Poly(methyl methacrylate), or Poly(ethylene terephthalate) [227], fluorinated polymers [228] and Polyimide [229] that contain unsaturated bonds. It was also extended to interfaces in nanocomposites [230,231]. A step forward with modelling approaches is being achieved with combining density functional theory and GW-BSE (GW-Belthe-Salpeter equation) in order to compute the optical properties of materials, in particular energy levels involved in excited states [232,233].…”
Section: Discussionmentioning
confidence: 99%
“…Trap states critically impact electronic transport in polymers and nanocomposites but can only be indirectly inferred from experimental measurements such as transient depolarization current (TSDC) and luminescence spectroscopy, making it difficult to account for their influence on breakdown strength in material design. We previously developed a framework for systematic first-principles predictions of trap states at filler-polymer interfaces and extracted the multi-modal distribution of trap states at polyethylene-silica interfaces expected to significantly influence the carrier transport [39].…”
Section: First-principles Predictions Of Trap Statesmentioning
confidence: 99%
“…Here, we extend that approach to predict trap states at the extrinsic interfaces of functionalized fillers, focusing on molecules thiophene, terthiophene, and ferrocene at the inorganic-polymer interface (Figure 3). We create an ensemble of 15 amorphous interfaces containing each molecule, starting from random-walk polymer structures and classical molecular dynamics quench simulations followed by first-principles structure optimization to account for the randomness in the interfacial structure [39]. We then perform electronic density-functional theory calculations using the JDFTx plane-wave basis code [40], PBE-GGE exchange-correlation functional [41] with DFT-D2 dispersion corrections, GBRV ultrasoft pseudopotentials [42], and a kinetic energy cutoff of 20 and 100 Hartrees on the wavefunction and charge density, respectively, for each of these 45 large interfacial structures, each with approximately 300 atoms and 1000 valence electrons.…”
Section: First-principles Predictions Of Trap Statesmentioning
confidence: 99%
“…The breakdown strength was estimated using an approach described in [15] which investigated the role of dispersion and volume fraction of spherical fillers on breakdown strength; that approach generalizes straightforwardly to fillers of arbitrary geometry. Briefly, this approach takes advantage of first-principles calculations of ensembles of amorphous polymer-nanofiller interfaces generated using molecular dynamics to provide critical information regarding trap distributions [18]. For example, we have shown that defects at polyethylene-silica interfaces exhibit a bimodal distribution of shallow and deep traps (Fig.…”
Section: Ecs Transactions 108 (2) 51-60 (2022)mentioning
confidence: 99%
“…(c) The carrier mobility is inversely correlated with the experimental breakdown strength, allowing us to calibrate breakdown strength predictions from mobility estimates[15]. (Adapted with permission from (a) Ref [18]. and (c) Ref [15].…”
mentioning
confidence: 99%